The Ethnic Composition Of Uzbeks And Tajiks In The Territory Of Afghanistan - Khojamurodov Nodirbek Sultonmurodovich (Genius Journals, 2026)
This article analyzes the ethnic composition of Uzbeks and Tajiks in the territory of Afghanistan, their history, geographical location, clans, and national characteristics. The study provides information on Afghanistan's multiethnic composition, population growth, major ethnic groups, and their areas of residence. In addition, the integration of Uzbeks and Tajiks with the local population, their cultural and interlingual interactions, customs, and national characteristics are highlighted
Keywords: Afghanistan; Uzbeks; Tajiks; ethnic composition